Buah Nanas (Ananas comosus L.) sebagai Faktor Penurunan Resiko Inflamasi Kronis pada Penyakit Infeksi - Muhammad Hidayatullah Saputra Amsia (CV. Jasa Sukses Abadi, 2020)
The inflammatory reaction is a defensive reaction (self-defense) in response to injury in the form of a vascular reaction which results in the delivery of fluids, dissolved substances and cells from the blood circulation to the interstitial tissues in the area of ​​injury or necrosis. Inflammation can also be included in a nonspecific reaction, from the host to infection. The result of an inflammatory reaction is the neutralization and removal of the invading agent, the destruction of the necrotic tissue, and the formation of the conditions necessary for repair and recovery. If the inflammatory process does not heal, it can lead to chronic inflammation. Pineapple (Ananas Comosus L.) contains the enzyme bromelain which is a proteolytic enzyme that has anti-inflammatory properties. The most common use of bromelain is as an anti-inflammatory and anti-edema agent, antithrombotic and fibrinolytic activity.5 Bromelain is categorized as a dietary supplement by the United States FDA and is on the list of compounds known to be safe. In addition, it is also reported that there are vanillin, methyl-propyl ketone, n-valerianic acid, isocapronic acid, acrylic acid, L (-) - malic acid, β-methyltiopropionic acid methyl ester (and ethyl ester), 5-hydroxytriptamine, quainic acid. -1, 4-di-p-coumarin. Pineapple can be used as a preventive measure for the occurrence of chronic inflammation in infectious diseases.